Changes in radiosensitivity induced by cyclic nucleotides and chemical radioprotection - Fremuth, F (Folia biologica, 1977)
Cyclic AMP has a radioprotective effect and its aministration results in a significant increase in LD50/30 values in Chinese hamsters. The efficiency of these radioprotective effects is comparable to that of such radioprotective compounds as AET and cystamine + mexamine. Cyclic GMP is responsible for significant radiosensitizing effects. Changes in radiosensitivity after administration of cyclic nucleotides are both immediate and delayed and correlate closely with dose and time of administration.
Keywords: Cyclic GMP; Cystamine; křečci praví; AMP cyklický; beta-Aminoethyl Isothiourea; zvířata; Radiation-Protective Agents; Radiation Tolerance; Animals; tolerance záření; Nucleotides, Cyclic; Theophylline; dibutyryl cyklický AMP; nukleotidy cyklické; cystamin; beta-aminoethylisothiomočovina; radioprotektivní látky; Bucladesine; guanosinmonofosfát cyklický; Cricetinae; Cyclic AMP; 5-Methoxytryptamine; 5-methoxytryptamin; theofylin